The Moderating Effects Of E-Government On The Relationship Between Administrative Decentralization And Service Delivery In County Governments In Kenya - Duncan M. Wagana; Mike A. Iravo; Joyce D. Nzulwa; John M. Kihoro (European Scientific Journal, ESJ, 2016)
This study sought to explore the relationship between the devolved governance aspect of administrative decentralization and service delivery in county governments in Kenya. The study also tested the moderating role of e-government on the relationship between administrative decentralization and service delivery in county governments in Kenya. The study used a sample size of 275 respondents, who are government officials drawn from 8 county governments in Kenya. The study used bivariate regression analysis and moderated multiple regression (MMR) to analyze the association between administrative decentralization, e-government, and service delivery variables. Based on the findings, a significant positive relationship between administrative decentralization and service delivery was established. However, the study found the moderating effect of e-government on the relationship between administrative decentralization and service delivery in county governments in Kenya to be insignificant. Finally, the study drew its conclusion and provided recommendations for future researchers.